Sistem Informasi Evaluasi Kualitas Layanan E-Learning Menggunakan Dimensi Servqual dan Fuzzy Kano Model untuk Meningkatkan Kepuasan Mahasiswa - Yoseph Pius Kurniawan Kelen; Haryati (JURNAL ILMU KOMPUTER, 2016)
Evaluation of e-learning is important to know the level of success of e-learning website. The results of the evaluation can be further improved on. The purpose of this research is to design information systems evaluation of e-learning by using Servqual dimensions and Fuzzy Kano Model. The method used in this research is to identify the criteria that affect the quality of service based on the dimensions of Servqual by using Fuzzy Kano, by providing functional and dysfunctional questions to respondents. Fuzzy method is used to reduce the subjectivity of respondents, which then classified each attribute in Kano categories namely: category must-be, one-dimensional, attractive, and indifferent. Results of the study was the evaluation of information systems that generate e-learning and student satisfaction category of needs mapping attributes in e-learning. A case study conducted on the website kulon.undana.ac.id showed that students were quite satisfied with the service on the dimensions Assurance (0.54), Empathy (0.53), Responsiveness (0.53), and Website Content (0.56 ) with the mapping category is Attractive. Students are not happy with the services that exist in the dimension Reliability (0.48) and the position of the category is Indifferent.